Low-cadmium rice (Oryza sativa L.) cultivar can simultaneously reduce arsenic and cadmium concentrations in rice grains. Issue 4 (3rd July 2016) - Ishikawa, Satoru; Makino, Tomoyuki; Ito, Masashi; Harada, Koji; Nakada, Hitoshi; Nishida, Ippei; Nishimura, Makoto; Tokunaga, Tetsuo; Shirao, Kensuke; Yoshizawa, Chieko; Matsuyama, Minoru; Abe, Tadashi; et al.
ABSTRACT: In previous research, we produced a japonica rice ( Oryza sativa L.) cultivar ('Koshihikari Kan No. 1') with nearly undetectable levels of cadmium (Cd) in the grains. In this study, we hypothesized that growing this cultivar aerobically would simultaneously reduce arsenic (As) and Cd concentrations in the grains. We grew this cultivar and 'Koshihikari', its parent, in paddy fields with different soil properties under three water regimes: flooded conditions (FLD), alternate wetting and drying conditions (AWD) and water-saving conditions (WAS). FLD for several weeks before and after heading significantly increased the grain As concentration in both cultivars. AWD, with the soil re-flooded just after disappearance of the ponded water, reduced grain As concentrations by an average of 27% relative to FLD for both cultivars. WAS, with irrigation after drying of the soil surface, decreased grain As concentrations by an average of 43.1% for 'Koshihikari Kan No. 1' and 48.2% for 'Koshihikari' compared to FLD. Although AWD and WAS remarkably increased grain Cd concentrations in 'Koshihikari', 'Koshihikari Kan No. 1' had nearly undetectable levels of grain Cd in all treatments. Compared with 'Koshihikari' in FLD, grain yield of 'Koshihikari Kan No. 1' and 'Koshihikari' decreased by averages of 2% for AWD and 4 to 6% for WAS. In addition, WAS tended to decrease grain quality slightly for both cultivars. Although aerobic conditions such as WAS have somewhat adverse effects on grain yield and quality, growing the low-Cd cultivar aerobically is the most practical way to simultaneously reduce Cd and As contents in the rice grains.